State Estimation for Cyber-Physical Systems with Communication Irregularities - Svenda, Vanja. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Electrical Engineering.; Advisor: Aleksandar Stankovic.; Committee: Ali Abur, Loring Tu, and Usman Khan.; Keyword: Electrical engineering.